Influencia de los radios en algunas propiedades físicas y mecánicas de la madera de ocho encinos (Quercus) de Durango, México - de la Paz Pérez Olvera, Carmen; Dávalos Sotelo, Raymundo; Quintanar Isaías, Paz Alejandra (Instituto de Ecología, A.C., 2016)
The relations between the radial parenchyma (uniseriate and multiseriate rays) and volumetric shrinkage and with the mechanical properties of eight Durango woods are presented. The mechanical properties studied are: static bending, compression parallel-to-grain, compression perpendicular-to-grain and shear parallel-to-grain. The relationship between the anatomical and physical properties 3 was determined through stepwise regression analysis. The dependent variables were the anatomical values and the independent ones were the physical and mechanical values. It was determined that the height and width of multiseriate rays are the anatomical characters with the greatest influence in all properties. It was concluded that the selection of oak wood species in the transformation processes is an urgent task and that the anatomical and physical characteristics that influence its management must be considered in order to utilize this resource in an optimal way and to be able to achieve the conservation of oak forests and the preservation of the ecological equilibrium of the places where they grow.